Dynamic contrast-enhanced magnetic resonance imaging may act as a biomarker for vascular damage in normal appearing brain tissue after radiotherapy in patients with glioblastoma. (November 2018) - Fahlström, Markus; Fransson, Samuel; Blomquist, Erik; Nyholm, Tufve; Larsson, Elna-Marie
Background: Dynamic contrast-enhanced magnetic resonance imaging (DCE-MRI) is a promising perfusion method and may be useful in evaluating radiation-induced changes in normal-appearing brain tissue. Purpose: To assess whether radiotherapy induces changes in vascular permeability (K trans ) and the fractional volume of the extravascular extracellular space (Ve ) derived from DCE-MRI in normal-appearing brain tissue and possible relationships to radiation dose given. Material and Methods: Seventeen patients with glioblastoma treated with radiotherapy and chemotherapy were included; five were excluded because of inconsistencies in the radiotherapy protocol or early drop-out. DCE-MRI, contrast-enhanced three-dimensional (3D) T1-weighted (T1W) images and T2-weighted fluid attenuated inversion recovery (T2-FLAIR) images were acquired before and on average 3.3, 30.6, 101.6, and 185.7 days after radiotherapy. Pre-radiotherapy CE T1W and T2-FLAIR images were segmented into white and gray matter, excluding all non-healthy tissue. K trans and Ve were calculated using the extended Kety model with the Parker population-based arterial input function. Six radiation dose regions were created for each tissue type, based on each patient's computed tomography-based dose plan. Mean K trans and Ve were calculated over each dose region and tissue type. Results: Global K trans and Ve demonstrated mostly non-significant changes with mean values higher for post-radiotherapy examinations in both gray and white matter compared to pre-radiotherapy. No relationship to radiation dose was found. Conclusion: Additional studies are needed to validate if K trans and Ve derived from DCE-MRI may act as potential biomarkers for acute and early-delayed radiation-induced vascular damages. No dose-response relationship was found.